2018
DOI: 10.1002/erv.2587
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the relationship between binge eating disorder and insomnia symptoms

Abstract: These findings suggest that depression, anxiety, and sleep are important constructs to consider in BED development and presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 55 publications
(74 reference statements)
4
15
1
1
Order By: Relevance
“…Consistent with the results of previous studies which administered the NEQ-14 (Vander Wal, 2012; Aloi et al, 2017), I-NEQ-16 scores were significantly associated with concurrent scores for binge eating, emotional and external eating, depressive and anxiety symptoms, and sleep-related problems (i.e., nocturnal chronotype and insomnia severity). Considering that NES is frequently comorbid with binge eating (Napolitano et al, 2001; Grilo and Masheb, 2004; Colles et al, 2007; Allison et al, 2008; McCuen-Wurst et al, 2018) and that binge eating severity has been associated with emotional psychopathology (Bulik et al, 2002) and insomnia (Kenny et al, 2018), we also calculated partial correlations between the I-NEQ-16 and concurrent measures, while controlling for the effect of binge eating severity, and found that this variable was not able to account for all the associations night eating severity has with anxiety, depression, and sleep-related problems (Runfola et al, 2014). Furthermore, the BMI score was weakly but statistically significantly associated with I-NEQ-16 scores only after controlling for the effect of binge eating severity.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the results of previous studies which administered the NEQ-14 (Vander Wal, 2012; Aloi et al, 2017), I-NEQ-16 scores were significantly associated with concurrent scores for binge eating, emotional and external eating, depressive and anxiety symptoms, and sleep-related problems (i.e., nocturnal chronotype and insomnia severity). Considering that NES is frequently comorbid with binge eating (Napolitano et al, 2001; Grilo and Masheb, 2004; Colles et al, 2007; Allison et al, 2008; McCuen-Wurst et al, 2018) and that binge eating severity has been associated with emotional psychopathology (Bulik et al, 2002) and insomnia (Kenny et al, 2018), we also calculated partial correlations between the I-NEQ-16 and concurrent measures, while controlling for the effect of binge eating severity, and found that this variable was not able to account for all the associations night eating severity has with anxiety, depression, and sleep-related problems (Runfola et al, 2014). Furthermore, the BMI score was weakly but statistically significantly associated with I-NEQ-16 scores only after controlling for the effect of binge eating severity.…”
Section: Discussionmentioning
confidence: 99%
“…All procedures were approved by the regional health research ethics board. Recruitment procedures are reported elsewhere (Kenny, Singleton, & Carter, 2017;Kenny, Van Wijk, Singleton, & Carter, 2018). Briefly, individuals with BED and NED were recruited from the community via social media, radio interviews, and posters.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, Kenny et al [60] showed that BED patients reported significantly greater insomnia symptoms than individuals without BED and that this relationship was partially and fully mediated by anxiety and depressive symptoms. This may imply that poor sleep that BED patients experience is related to mood.…”
Section: Binge Eating Disordermentioning
confidence: 99%